Redistribution of CD8+ T cell subsets in metastatic renal cell carcinoma patients treated with anti‐PD‐1 therapy. Issue 7 (4th May 2022) - De Biasi, Sara; Guida, Annalisa; Lo Tartaro, Domenico; Fanelli, Martina; Depenni, Roberta; Dominici, Massimo; Finak, Greg; Porta, Camillo; Paolini, Annamaria; Borella, Rebecca; Bertoldi, Carlo; Cossarizza, Andrea; et al.
Abstract: Renal‐cell carcinoma (RCC) is responsible for the majority of tumors arising from the kidney parenchyma. Although a progressive improvement in median overall survival has been observed after the introduction of anti‐PD‐1 therapy, many patients do not benefit from this treatment. Therefore, we have investigated T cell dynamics to find immune modification induced by anti‐PD‐1 therapy. Here, we show that, after therapy, RCC patients (5 responders and 14 nonresponders) are characterized by a redistribution of different subsets across the memory T cell compartment. Abstract : Peripheral T cell dynamics was investigated in 19 metastatic renal cancer carcinoma (RCC) patients undergoing anti‐PD1 therapy by applying 28‐parameter flow cytometry panel and unsupervised analysis algorithm called Full Annotation Using Shaped‐constrained Trees (FAUST). Therapy induced a redistribution of different subsets across the memory CD8+ T cell compartment.